LINEN SIEVES – THOUGHTS ON THE MARGIN OF ANGI ISTVÁN'S MUSICOLOGICAL WRITINGS (ANGI ISTVÁN: SITE DE IN, EDITURA MEDIA MUSICA, CLUJ-NAPOCA, 2014) - FODOR, Attila (Studia Universitatis Babes-Bolyai Musica, 2014)
Founder of the Romanian school of music aesthetics, Angi Ştefan exposes in this book a bounded, but significant segment of his central musicological concerns of the late years. Its unconventional title Linen sieves, refers to a paradigmatic verse of the Transylvanian poet, Lucian Blaga, called At the Court of Yearning. Both provocative and meditative, the title-metaphor invites the reader not only to explore the content of this book, but also to familiarize itself with the significant and original aesthetic view of the author, elaborated in a two-volume treatise, Lectures on Music Aesthetics (Oradea University Press, 2004.)